Facebook as a Tool in University English Language Education - Šliogerienė, Jolita; Masoodi, Marjan; Gulbinskienė, Dalia (Acta Paedagogica Vilnensia, 2016)
Over the past several years, there has been an explosion in the availability and widespread use of social media sites such as Facebook, Twitter, and YouTube. This study evaluates the potentially relative effectiveness of Facebook as one of the most popular social networks applied for the development of English language skills, fostering metacognitive awareness and promoting learner autonomy by Lithuanian intermediate EFL learners in university settings. To this end, 63 intermediate EFL learners were questionnaired to express their beliefs about the use of Facebook and to assess their views on the improvement of language skills and motivation in English language learning, fostering their metacognitive confidence, attitudes and sense of autonomy towards English language learning. The research revealed that applying Facebook by learners improves their language skills and promotes their sense of autonomy.